Human and mouse XAP-5 and XAP-5-like (X5L) genes: identification of an ancient functional retroposon differentially expressed in testis - Sedláček, Zdeněk; Münstermann, Ewald; Otto, Christiane; Schütz, Günther; Poustka, Annemarie (Genomics, 1999)
Although most retroposons that arose by reverse transcription of cellular mRNAs and by reintegration into the genome are nonfunctional, several examples exist in which the retroposon acquired a novel function and became fixed in the genome as a functional gene. We identified another such case: the ubiquitously expressed X-linked XAP-5 gene with unknown function gave rise to its retroposed counterpart, XAP-5-like (X5L), which has an intronless open reading frame and is autosomal in human. Phylogenetic analysis of the human and mouse XAP-5 and X5L genes shows that the retroposition most likely took place before the radiation of eutherian mammals. The XAP-5 and X5L genes are expressed in a wide range of tissues but are differentially expressed in testis. The ancient origin and broad expression of the X5L retroposon indicate that the XAP-5 and X5L genes may have assumed different functions in somatic cells. In addition to this, because of its autosomal location and its high level and particular pattern of expression in spermatogenic cells, the X5L expression in testis may compensate for the X-linked XAP-5 gene, which may be silenced during spermatogenesis.